74.7k views
0 votes

(3)/(5) x-(1)/(3) x=x-1

2 Answers

5 votes

Answer:

Exact Form:

x = 15/11

Decimal Form:

x = 1.36

Mixed Number Form:

x = 1(4)/(11)

Explanation:

(3)/(5)x-(1)/(3)=x-1

Simplify (3)/(5)x-(1)/(3)x

(4x)/(15)=x-1

Move all terms containing x to the left side of the equation.

-(11x)/(15)=-1

Multiply both sides of the equation by -(15)/(11)

-(15)/(11)(-(11)/(15))= -(15)/(11) . -1

Simplify both sides of the equation.

(15)/(11)

The result can be shown in multiple forms.

Exact Form:

x = 15/11

Decimal Form:

x = 1.36

Mixed Number Form:

x = 1(4)/(11)

User HSJ
by
5.0k points
5 votes

Answer:

As an improper fraction:
15/11

As a mixed number:
1 (4)/(11)

As a decimal: 1.36

Explanation:


3/5x - 1/3x = x - 1

Find a common denominator between 5 and 3 (15)


(3 * 3) / 15x - (1 * 5) / 15 = x - 1


9/15x - 5/15 = x - 1

Subtract the fractions


4/15x = x - 1

Subtract x from both sides of the equation


-11/15x = -1

Multiply both sides of the equation by 15/-11 to simplify

x = 15/11

Hope this helps :)

User Amaala
by
4.6k points